Palladium Nanoparticles Encapsulated in a Silicalite‐1 Zeolite Shell for Size‐Selective Catalysis in Liquid‐Phase Solution. Issue 7 (25th February 2016) - Liu, Chang; Liu, Jian; Yang, Shuliang; Cao, Changyan; Song, Weiguo
Abstract: Size‐selective catalysis is of great significance in both fundamental research and industrial applications. One well‐known example is zeolite‐based catalysts, which show remarkable size selectivity in gas‐phase reactions. However, very few of these catalysts are realized in liquid‐phase solution. Herein, we report an efficient route to produce a composite composed of Pd nanoparticles encapsulated in a silicalite‐1 zeolite shell. This composite shows sharp size‐selective catalysis in the hydrogenation of olefin aldehydes in aqueous solution. Owing to the pore‐size limitation of the silicalite‐1 zeolite shell (0.53×0.56 nm), the catalyst shows high activity in the hydrogenation of 3‐methyl‐2‐butenal (0.38×0.62 nm) and cinnamaldehyde (0.54×0.92 nm) but no activity for the hydrogenation of 3, 3‐diphenylacrylaldehyde (0.81×1.0 nm). A catalyst with this type of structure can be applied to load other metal nanoparticles and can serve as a useful platform to study heterogeneous size‐selective catalysis in liquid solution. Abstract : Heroes in a zeolite shell : An efficient route is developed to produce a composite consisting of Pd nanoparticles encapsulated in a silicalite‐1 zeolite shell (Pd@S‐1). This composite shows sharp size‐selective catalysis in the hydrogenation of olefin aldehydes in aqueous solution. A catalyst with this type of structure can be applied to load other metal nanoparticles and can serve as a useful platform to study heterogeneous size‐selective catalysis in liquid solution.